Occurrence of Surface Water Contaminations: An Overview. (April 2018) - Shahabudin, M M; Musa, S
Abstract: Water is a part of our life and needed by all organisms. As time goes by, the needs by human increased transforming water quality into bad conditions. Surface water contaminated in various ways which is pointed sources and non-pointed sources. Pointed sources means the source are distinguished from the source such from drains or factory but the non-pointed always occurred in mixed of elements of pollutants. This paper is reviewing the occurrence of the contaminations with effects that occurred around us. Pollutant factors from natural or anthropology factors such nutrients, pathogens, and chemical elements contributed to contaminations. Most of the effects from contaminated surface water contributed to the public health effects also to the environments.